Unsaturated bond recognition leads to biased signal in a fatty acid receptor - Mao, Chunyou; Xiao, Peng; Tao, Xiao-Na; Qin, Jiao; He, Qing-Tao; Zhang, Chao; Guo, Sheng-Chao; Du, Ya-Qin; Chen, Li-Nan; Shen, Dan-Dan; Yang, Zhi-Shuai; Zhang, Han-Qiong; et al. (Science (American Association for the Advancement of Science), 2023)
Individual free fatty acids (FAs) play important roles in metabolic homeostasis, many through engagement with more than 40G protein–coupled receptors. Searching for receptors to sense beneficial omega-3 FAs of fish oil enabled the identification of GPR120, which is involved in a spectrum of metabolic diseases. Here, we report six cryo–electron microscopy structures of GPR120 in complex with FA hormones or TUG891 and G i or G iq trimers. Aromatic residues inside the GPR120 ligand pocket were responsible for recognizing different double-bond positions of these FAs and connect ligand recognition to distinct effector coupling. We also investigated synthetic ligand selectivity and the structural basis of missense single-nucleotide polymorphisms. We reveal how GPR120 differentiates rigid double bonds and flexible single bonds. The knowledge gleaned here may facilitate rational drug design targeting to GPR120. In addition to being an energy source, fatty acids influence cells through their effects on membrane structure and as signaling molecules or precursors to signaling molecules. The G protein–coupled receptor GPR120 binds to various fatty acids, in particular polyunsaturated omega-3 fatty acids, which are essential components of the human diet. Mao et al . determined cryo–electron microscopy structures of GPR120–G protein complexes bound to natural lipids or a synthetic agonist and, in parallel, performed biochemical experiments to study biased signaling properties of the receptor. The tight binding pocket packs around the lipids, and hydrophobic and aromatic residues read out different double bonds, resulting in subtle structural changes that result in different activation and bias patterns for different ligands. These insights will be invaluable for efforts to target this receptor for drugs that treat metabolic and immune diseases. —MAF Structures and biochemistry reveal how free fatty acid receptors recognize and respond to agonists.